Microbial Antagonism Toward Botrytis Bunch Rot of Grapes in Multiple Field Tests Using One Bacillus ginsengihumi Strain and Formulated Biological Control Products - Calvo-Garrido, Carlos; Roudet, Jean; Aveline, Nicolas; Davidou, Ludivine; Dupin, Sévérine; Fermaud, Marc (Frontiers in Plant Science, 2019)
Botrytis bunch rot (BBR), caused by the necrotrophic fungus Botrytis cinerea, is a major disease of wine and table grapes worldwide. Due to negative effects of pesticides on the environment and human health, alternative control strategies against BBR, such as biological control agents (BCAs), are required to produce high-quality grapes and wines with high standards of food safety. However, few biological control products against BBR are available, and their efficacy is sometimes variable. This study aimed to evaluate and compare 1) the efficacy of new bacterial BCA strains developed at INRA Bordeaux and 2) the BBR reductions achieved by commercial biocontrol products that are already registered or close to being registered. During three consecutive seasons, 10 field experiments were established in six different experimental vineyards in southwestern France. Spray applications were performed at key phenological stages (five or six during the season), or at high BBR-risk periods late in the season according to a Disease Risk Index model. At harvest, BBR incidence and severity (% of symptomatic berries per bunch) were visually determined. The experiments included four bacterial strains at an early experimental stage, particularly Bacillus ginsengihumi (S38). Nine commercial BCA products were also tested, including Bacillus subtilis, Bacillus amyloliquefaciens, Aureobasidium pullulans, Ulocladium oudemansii, and Candida sake. Among the four experimental bacterial strains, only B. ginsengihumi S38 significantly controlled the BBR, presenting reductions in the average severity ranging from 35% to 60%, compared to untreated control, throughout the three seasons. Several commercial BCAs achieved significant reductions in BBR severity ranging from 21% to 58%, although not in every trial. The treatments that achieved higher reductions in severity rates were based on C. sake (45%), B. subtilis (54%), and B. amyloliquefaciens (58%). The efficacy of those BCAs was consistent throughout the studied seasons. The results confirmed the suitability of several biological control products under the conditions in vineyards in southwestern France, while also highlighting the good performance of the novel experimental BCA B. ginsengihumi S38 strain, which achieved similar control rates to the products registered for commercial use. The major factors involved in the variability in the results are also discussed.